2018
DOI: 10.1088/1361-6528/aabd90
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing residues and strain in 2D materials transferred from PDMS

Abstract: Integrating layered two-dimensional (2D) materials into 3D heterostructures offers opportunities for novel material functionalities and applications in electronics and photonics. In order to build the highest quality heterostructures, it is crucial to preserve the cleanliness and morphology of 2D material surfaces that come in contact with polymers such as PDMS during transfer. Here we report that substantial residues and up to ∼0.22% compressive strain can be present in monolayer MoS transferred using PDMS. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
131
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(145 citation statements)
references
References 54 publications
3
131
0
Order By: Relevance
“…The glue residues mainly depend on different tapes, for the white tape (3 M scotch) or blue tape (Nitto), there will be some glue left on substrate, which can be removed by further annealing if required by the subsequent measurement. However, we can also use home-made polydimethylsiloxane (PDMS) to replace these tapes as transfer media, which can make the substrate much cleaner 54 . The thickness of Au/Ti layer is a crucial factor.…”
Section: Methodsmentioning
confidence: 99%
“…The glue residues mainly depend on different tapes, for the white tape (3 M scotch) or blue tape (Nitto), there will be some glue left on substrate, which can be removed by further annealing if required by the subsequent measurement. However, we can also use home-made polydimethylsiloxane (PDMS) to replace these tapes as transfer media, which can make the substrate much cleaner 54 . The thickness of Au/Ti layer is a crucial factor.…”
Section: Methodsmentioning
confidence: 99%
“…These two peak positions are slightly smaller than those from strain‐free 2D Te flakes with similar thickness. [ 77–80 ] Such a slight shift for the A 1 ‐mode and E 2 ‐mode peaks is likely due to the existence of residual stress introduced from the transfer [ 81 ] and LB assembly [ 82–84 ] processes. In our experiment, we maintain the same parameters for all transfer and LB assembly steps.…”
Section: Figurementioning
confidence: 99%
“…1a). The stamping process mediated by PDMS lm is simple to perform and was widely adapted in many prior studies (Dean et al 2010;Jain et al 2018;Rosenberger et al 2018). In particular, the PDMS-based stamping process has been primarily used to fabricate 2D vertical heterostructures (Dean et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Previous TEM investigations revealed that 2D crystals prepared using various sample preparation processes suffer from surface contamination In this study, we explored the potential of using atomic force microscopy (AFM) to remove surface residues from 2D crystals (Goossens et al 2012;Jain et al 2018;Lindvall et al 2012;Rosenberger et al 2018; Schweizer et al 2020). Using various TEM investigations, we con rmed that polydimethylsiloxane (PDMS) residues on graphene samples are effectively removed by contact-mode AFM sweeping.…”
Section: Introductionmentioning
confidence: 99%